PERAN BIDANG KBKK DAN OBSERVASI MAGANG DALAM UPAYA PERCEPATAN PENURUNAN ANGKA STUNTING DI KOTA DENPASAR - Ni Made Ayu Mega Mustika; Gusti Ketut Purnama Yanti; Afrida Kanata; Elisabet Malo; I Ketut Nada Cahyadi Putra; Ni Komang Sri Yuliastini (Sewagati, 2025)
Reducing stunting prevalence is a national priority in Indonesia, including in Denpasar City, which continues to accelerate its efforts through cross-sectoral collaborative programs. This article aims to analyze the role of the Division of National and Family Resilience (KBKK) and internship observation activities in supporting stunting reduction efforts. This study employed a qualitative descriptive approach through field observations during the internship program, interviews with KBKK officers, and reviews of government documents related to stunting reduction initiatives. The findings indicate that KBKK plays an essential role in strengthening family education, mapping stunting cases, assisting at-risk families, and enhancing synergy between cadres, internship students, and local health centers. Student involvement significantly improves program effectiveness through direct observation, family assistance, nutrition education, and field data collection that supports case validation for children under five and pregnant women. This collaboration not only enhances students’ understanding of public health issues but also increases the local government’s capacity to identify risks and accelerate interventions. Overall, the synergy between KBKK and internship activities provides substantial contributions to the acceleration of stunting reduction efforts in Denpasar City.